Complete and complete moment convergence for i.i.d. random variables under exponential moment conditions. Issue 9 (3rd May 2017) - Dehua, Qiu; Pingyan, Chen
ABSTRACT: In this paper, we establish a complete convergence result and a complete moment convergence result for i.i.d. random variables under moment condition which is slightly weaker than the existence of the moment generating function. The main results extend and improve the related known results of Lanzinger (1998 ) and Gut and Stadtmüller (2011 ).